Frequency of Dyslipidemia and its Associated Factors in patients of Chronic Liver Disease - Ahmed Adnan, Shahid Bilal, Muhammad Abdul Raziq, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chronic liver disease (CLD) refers to a group of liver conditions in which normal liver tissue is gradually replaced by fibrotic tissue. Various metabolic disturbances often accompany CLD, including lipid abnormalities, clotting factor deficiencies, and sometimes venous thromboembolism due to reduced anticoagulant factors. Dyslipidemia is one such disturbance and occurs when there is an imbalance in lipids or lipoproteins. Due to the variability in findings from earlier studies, the present study aimed to find out the frequency of dyslipidemia and its associated factors in chronic liver disease patients. Methods: A descriptive, cross-sectional study was conducted at the department of medicine, Bahawal Victoria Hospital, Bahawalpur during February to August 2023. Total 195 patients were included in the study. After taking informed written consent, 5 ml blood sample of each patient was sent to the institutional pathology laboratory for measurement of lipid profile and presence or absence of dyslipidemia. All the data was entered and analyzed by using Statistical Package for Social Science (SPSS) version 22. Anova with Post-hoc Tuckey test was used to find out the association of effect modifiers with lipid profile. P-value ≤0.05 was considered as significant. Results: The mean age of the study participants was 39.44 ± 9.91 years. About 82.05% were male and 17.94% were females and majority (56.92%) were having BMI in between 25-30kg/m2. Mean duration of disease was 1.67 ± 0.72 years. About 28.2% participants were known case of hypertension while 36.41% were diagnosed case of diabetes. Looking over the serum lipid profile the mean with standard deviation of HDL, LDL, cholesterol and triglycerides were 37.34 ± 4.12mg/dL, 77.24 ± 22.97 mg/dL, 152.31 ± 24.59 mg/dL and 101.58 ± 24.48 mg/dL, respectively. The mean with standard deviation of HDL, LDL, cholesterol and triglycerides were having statistically non-significant association with the factors like age, gender, BMI, disease duration, history of hypertension and diabetes but severity of disease, as per Child-Pugh classification, showed significant association with the mean values of all variables of lipid profile. Conclusion: A considerable proportion of patients with chronic liver disease demonstrated dyslipidemia, and its occurrence varied according to disease severity as assessed by the Child-Pugh classification. Current data indicate that lipid parameters may play a significant role in the risk assessment and therapeutic planning of CLD patients. Keywords: Chronic liver disease, Dyslipidemia, Child-Pugh Classification.